Machiavellianism in Indian management - Cyriac, K. (Journal of business ethics, 1994)
Machiavellianism has tremendous influence on modern business communities, especially in the U.S.A. and European countries. Businessmen today, it is said, prefer to follow the directions of pragmatism and expediency rather than the dictates of individual conscience., In principles and practices, Indian management by and large follows the Western line. Therefore, the question arises whether Machiavellian influences are perceptibly high on Indian managers. This question is more relevant in the light of a few surveys conducted on the ethical attitudes of Indian managers. These identified a clear contrast between their expressed behaviour and wanted attitudes. The present study on the attitudes of managers from the major cities of India concludes that Niccolo Machiavelli inspires and influences Indian managers, but has not become the final determinant in their decision-making.